ANALISIS PROSES PEMBELAJARAN MATEMATIKA PADA MATERI GARIS DAN SUDUT - RAHAYU, SARAH SRI (Jurnal Ilmu Pendidikan Indonesia, 2020)
This study aims to find out an overview of how the mathematics learning process on lines and angles in class VII SMP YPK 2 Manokwari, the level of teacher readiness, and to obtain an overview of the implementation of student-centered learning through the contextual learning model that takes place at SMP YPK 2. Manokwari on lines and angles. The method used in this research is descriptive method with a qualitative approach. The results showed that (1) The learning process of mathematics at SMP YPK 2, especially in the material of lines and angles, has gone well in accordance with the learning plan that has been made and in accordance with the learning steps, namely introduction, core activities, closing, and evaluation (2 ) The readiness of the teacher in preparing for learning is good (3) The implementation of learning that is centered on students through the contextual learning model has not been fully carried out due to time constraints and differences in the abilities of each student which are not the same as the lack of existing facilities and infrastructure